Evaluasi Faktor-Faktor Yang Mempengaruhi Kinerja Personel Dalam Konteks Lingkungan Kerja Yang Dinamis - Filippus Cahyo Setyawan; Sri Sundari; Marisi Pakpahan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to evaluate the factors influencing personnel performance in the context of a dynamic work environment. The background of the study is rooted in the challenges organizations face amid rapid changes and the complexity of the modern work environment. The research methodology employs a combination of literature analysis and empirical research to identify significant variables that either enhance or hinder personnel performance. Research findings indicate that adaptive leadership, organizational flexibility, and individual skill development play pivotal roles in achieving optimal performance in a dynamic work environment. The implications of these research results provide insights for organizations to develop more effective strategies in managing personnel performance amidst constant change.